Building a Sustainable Workforce through Work-Life Integration: Antecedents, Consequences, and Implications - Jihan Abbada; Maulyta Wira Asti; Intan Ratna Wati (Arthatama: Journal of Business Management and Accounting, 2025)
This study presents a systematic review of the antecedents and consequences of Work-Life Integration (WLI) in the era of workplace flexibility and digitalization. WLI is a concept that describes how individuals harmonize work and personal life without rigid boundaries. Utilizing the PRISMA framework, a total of 27 articles were reviewed following screening and eligibility assessment stages. Thematic analysis revealed four categories of WLI antecedents: (1) organizational factors such as schedule flexibility, mentoring, and leave programs; (2) socio-demographic factors including generational differences and family structure; (3) individual factors such as resilience and emotional reflexivity; and (4) digital technology factors, which play a crucial role in supporting the implementation of WLI by enabling greater work flexibility and facilitating communication and collaboration regardless of time and location. The positive consequences of WLI include enhanced psychological well-being, job satisfaction and engagement, productivity, loyalty, as well as career advancement and equality. Conversely, without proper implementation and supportive management policies, WLI may pose several challenges in practice, such as technostress, role conflict, and social isolation. These findings show that WLI is an emerging approach in response to changes in the modern workplace, with its effectiveness influenced by the synergy between organizational policies, individual capabilities, and digital technology management.